Penerapan E-Government Dalam Peningkatan Kinerja Pegawai (Studi Kasus Aplikasi Bipang di Kelurahan Pattunuang Kota Makassar) - Nurdin Khaliq Sadewa; Jusman, Jusman; Abdul Mahsyar (Prosiding SISFOTEK, 2023)
The implementation of E-Government or electronic government has become an integral part of efforts to modernize public administration in various countries, especially in Indonesia. This study aims to determine the application of the E Government, especially through the Bipang application, in improving employee performance in Pattunuang Village, Makassar City. This type of research uses qualitative descriptive with a case study approach, namely collecting data through interviews, surveys, observations and document analysis related to the implementation of Bipang. The results of this research reveal several important findings. First, the implementation of Bipang has resulted in increased efficiency in the administrative process in Pattunuang Subdistrict, seen from the quality of employee performance, which is very influential because of better employee work patterns, in terms of quantity of employee performance in implementing e-government to This Bipang application can be seen from the process of completing work always on time according to the workload given by the leadership so that good cooperation is built in improving employee performance. Judging from the punctuality, it was found that Pattunuang sub-district employees always use the Bipang application in filling out absenteeism based on the location where they work. However, there are several obstacles that were also identified in this research, namely the need to update the system and the availability of infrastructure such as network access must be adequate in this Bipang application system. Apart from that, it is still needed to exercise additional and technical support to maximize the benefits of the Bipang application. In order to improve employee performance and the effectiveness of E-Government in Pattunuang District, the proposed recommendations include increasing training for employees, improving data security, and active promotion of the Bipang application to the public.